Resistensi Tokoh Perempuan dalam Cerpen Lesung Pipit Karya Eka Kurniawan: Feminisme Kekuasaan Naomi Wolf - Nensilianti, Nensilianti; Ridwan, Ridwan; Sakti M, Reztu Dwi (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2025)
This research aims to analyze the resistance of female characters reflected in the short story Lesung Pipit by Eka Kurniawan using the feminism of power approach. With a focus on rejection, resistance and action. This research identifies resistance carried out by female characters in short stories. The qualitative method used is by analyzing the content of the short story text and utilizing Naomi Wolf's concept of power feminism as an analytical framework. Through reading, note-taking, and dialectical analysis techniques, the data were collected and analyzed in three stages: data reduction, data presentation, and conclusion drawing. The results of the study reveal that the resistance of female characters in Lesung Pipit is reflected through the process of resistance formation and the treatment of Lesung Pipit as a strong woman. The main findings show that the characters resist through direct action and rejection of injustice and patriarchal treatment. The research provides an in-depth understanding and also a depiction of how Lesung Pipit internally and externally resists the social structure that oppresses her, reflecting the struggle of women in a patriarchal society.